A Case Study of the Relationship Between Vegetation Coverage and Urban Heat Island in a Coastal City by Applying Digital Twins - Qi, Yansu; Li, Han; Pang, Zonglin; Gao, Weijun; Liu, Chao (Frontiers in Plant Science, 2022)
While urban vegetation affects the urban thermal environment directly, the effects of different plant layouts and vegetation cover on urban microclimate regulation are different. This study has applied digital technologies to advance urban environmental research and forestry analysis. With a focus on a coastal city located on the eastern coast of the North Temperate Zone as a study area, this study collected the Landsat archive satellite remote sensing image data covering the study area in 2000–2020 and analyzed the temporal and spatial distribution characteristics of vegetation coverage, land surface temperature, and urban heat island (UHI) ratio index. The study results included the following findings: (1) The area of high fractional vegetation cover (FVC) (0.8–1.0) in the study area is increasing. Those areas are located in the mountain forests in the near-coastal area. The lowest temperature was also detected in the mountain area. (2) The distance from the coastline causes a negative correlation between land surface temperature and FVC. The land surface temperature in the regions with a distance of more than 25 km from the coastline decreases obviously with increasing FVC in summer. However, the correlation between the land surface temperature and FVC showed a slight change in the winter period. (3) UHI ratio index decreases along with the area of high FVC (H-FVC) area. The influence of ocean climate on seasons is different, which results in the reduced effect of the H-FVC area and differences in the UHI ratio index. (4) The distance from the coastline should be considered as an important factor in the forestry development planning of the coastal cities.